Feeding high-moisture corn grain silage to broilers fed alternative diets and maintained at different environmental temperatures - Cruz-Polycarpo, V. C. [UNESP]; Sartori, J. R. [UNESP]; Goncalves, J. C. [UNESP]; Pinheiro, D. F. [UNESP]; Madeira, L. A. [UNESP]; Polycarpo, G.; Zanetti, L. H.; Santos, T. S. [UNESP]; Pezzato, A. C. [UNESP] (Facta-fundacio Arnco Ciencia Tecnologia Avicolas, 2014)
The effects of the dietary substitution of dry corn by high-moisture corn grain silage (HMCGS) were evaluated on the performance, nutrient digestibility and serum biochemical parameters of broilers reared in an alternative production system and submitted to different environmental temperatures. A total of 288 one-day-old male Cobb chicks were distributed according to a randomized block design in a 3x4 factorial arrangement: three environmental temperatures (hot, thermoneutral or cold) and four levels of HMCGS in substitution of dry corn (0%, 20%, 40% or 60%). The acid analysis showed that the evaluated HMCGS contained average percentage values of ethanol, lactic acid, and acetic acid (expressed in 100% of dry matter) of 0.7690, 2.7320 and 0.0249%, respectively. Propionic and butyric acids were not detected. Dry corn and HMCGS presented pH values of 5.8 and 3.3, respectively. The inclusion of HMCGS reduced dietary pH, as shown by the values of 5.7, 5.4, 5.1 and 4.8 recorded for the diets containing 0%, 20%, 40% and 60% of HMCGS, respectively. There was no significant interaction between diets and environmental temperature. HMCGS may replace up to 40% dry corn in broiler diets when performance, triglyceride levels, and HDL-cholesterol ratio is considered, and up to 60% when nutrient digestibility is evaluated. High environmental temperature impairs broiler performance, nutrient digestibility, and serum biochemistry, demonstrating the influence of environmental temperature on broiler metabolism and performance.
Keywords: Absorption; Alternative feeds; Poultry; Cholesterol; Metabolism; Triglycerides